2020
DOI: 10.1038/s41593-019-0567-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporally restricted dopaminergic control of reward-conditioned movements

Abstract: Midbrain dopamine (DA) neurons encode both reward and movement-related events, and are implicated in disorders of reward processing as well as movement. Consequently, disentangling the contribution of DA neurons in reinforcing versus generating movements is challenging and has led to lasting controversy. We dissociated these functions by parametrically varying the timing of optogenetic manipulations in a Pavlovian conditioning task, and examining the influence on anticipatory licking prior to reward delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 56 publications
(99 reference statements)
10
69
1
Order By: Relevance
“…Activation of dopamine neurons both in VTA and SNc are known to reinforce preceding behaviors (Ilango et al, 2014;Keiflin et al, 2019;Lee et al, 2020;Saunders et al, 2018). The differences in dopamine axon signals that we observed in instrumental behaviors can provide specific constraints on the behaviors learned through dopamine-mediated reinforcement in these striatal regions.…”
Section: Discussionmentioning
confidence: 76%
“…Activation of dopamine neurons both in VTA and SNc are known to reinforce preceding behaviors (Ilango et al, 2014;Keiflin et al, 2019;Lee et al, 2020;Saunders et al, 2018). The differences in dopamine axon signals that we observed in instrumental behaviors can provide specific constraints on the behaviors learned through dopamine-mediated reinforcement in these striatal regions.…”
Section: Discussionmentioning
confidence: 76%
“…As a result, it is impossible to distinguish NLRP3 inflammasome activity directly related to inclusion of the hyperactivated transgene from wild-type NLRP3 inflammasome activity in glia resulting from the neuronal perturbation. For this reason, we are unable to determine with certainty that the Nlrp3 L351P allele was not expressed inappropriately in glia, although we believe this to be unlikely due to previous studies utilizing this strain and our characterization of microglia and astrocytes [ 49 52 ]. Despite the shortcomings of this model system, the inclusion of an endogenous Nlrp3 allele was likely a critical factor in our discovery of an expanding neuroinflammatory phenotype resulting from expression of the Nlrp3 L351P allele of neurons, a finding of importance as we work to understand the earliest stages of neuroinflammation in neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 90%
“…006660). The Slc6a3 IRESCre strain is now convincingly validated and in wide use [ 49 – 51 ], originally characterized using the ROSA reporter line to express CRE specifically within neuronal populations of the mesencephalon [ 52 ]. This process generated mice that selectively express the hyperactive Nlrp3 alleles only when the endogenous murine Nlrp3 gene is expressed in dopaminergic neurons.…”
Section: Methodsmentioning
confidence: 99%
“…One explores the direct effect of DA signal on NMDARs and VGCCs [12], and the other models DA-delay dependence in Ca 2+ dynamics through a Ca 2+ buffer [13]. However, those models predict 100-ms and 20-s time windows, respectively, and it still remains obscure about the mechanisms of the in-between time window of~2 s, which is required for DA-mediated reward conditioning [14]. Further, a pharmacological experiment showed that RP depends on the other type of AC, Ca 2+ -sensitive type 1 AC (AC1) [4], which is also expressed in the striatum [15].…”
Section: Introductionmentioning
confidence: 99%